Automatic accident detector and reporting system (hardware and software) ECBA medical system - Mohammed, Abdulrahman Taha; Kamsani, Noor Ain (IEEE, 2017)
Nowadays, the increase of using vehicles on the roads may impose several issues in delivering emergency help during an accident of which may threaten human lives involved greatly. During the accident, many people may lose their lives because of the delayed medical services, or the ambulance is stuck in traffic jam, and accident victims might die while waiting for the first aid kits and medical assistance. In this work, we propose a solution in providing the medical assistance and first aid kits before the arrival of the ambulance, coined as ECBA (Everyone Can be Ambulance). ECBA system is a software and a hardware system that works together for accident detection, report and medical assistance system. It is designed to provide automatic accident reporting system and to save people's lives.